Adapting for the future: flexibility of UK postgraduate training. Issue 10 (October 2020) - Mitchell, Tim
Abstract: Postgraduate surgical training has undergone repeated reforms alongside changes in terms of employment. The broad structure of progression from Foundation years through core and specialist training to the award of a Certificate of Completion of Training is likely to continue for the foreseeable future. Technological developments including robotics, genomics and artificial intelligence together with an extension of the surgical team are likely to alter dramatically the nature of surgery in the future. Surgical training will need to incorporate training in new technologies, including simulation, which will be provided in the workplace, academic institutions and commercial facilities. There will be greater emphasis on non-technical skills and human factors, especially in relation to the use of new technologies and working in wider teams, including non-medical staff. Genomics will play an increasing role in determining individualized patient care, with a need for surgeons to have an understanding of this field and communicate this to their patients. Surgical training will need to be suitably flexible in order to accommodate these developments, to allow more part-time working and portfolio careers, and to encourage recruitment and retention.